Ferritic stainless steel for denitration device

CN122953328APending Publication Date: 2026-10-20JFE STEEL CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202480089694.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-21
Filing Date
2024-11-08
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

但是,在高温下分解尿素水而生成氨的过程中,或未反应的尿素水挥发时,会生成氨基甲酸铵等物质,其会腐蚀不锈钢

Benefits of technology

[0046]根据本发明,能够提供一种在脱硝装置的使用环境中具有优异的耐腐蚀性的脱硝装置用铁素体系不锈钢。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The purpose of this invention is to provide a ferritic stainless steel for denitrification devices that exhibits excellent corrosion resistance in the operating environment of denitrification devices. A ferritic stainless steel for denitrification devices comprises, by mass%, C: 0.003–0.030%, N: less than 0.030%, Si: 0.20–1.00%, Mn: 0.05–0.50%, P: less than 0.050%, S: less than 0.020%, Cr: 13.0–21.0%, Mo: 0.001–3.00%, Al: 0.001–0.50%, Nb: 0.001–0.60%, Ti: 0.001–0.15%, satisfying the following formulas (1) and (2), with the remainder consisting of Fe and unavoidable impurities. (Ti+Nb×47 / 97) / (8×(C+N)) ≥ 1.0 ...(1;Cr-12Nb-2.0Mo-Si ≥ 10.0 ...(2)。 In formulas (1) and (2), Ti, Nb, C, N, Cr, Mo and Si represent the content (mass%) of each element.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a ferritic stainless steel for denitrification devices, and more particularly to ferritic stainless steel used in denitrification devices such as urea SCR (Selective Catalytic Reduction) for removing nitrogen oxides (NOx) from exhaust gases in automobiles, ships, and thermal power plants. Background Technology

[0002] In recent years, from the perspective of global environmental protection, there has been a demand to strengthen waste gas purification. Therefore, the application of denitrification devices such as urea-based SCR systems is expanding.

[0003] Here, urea SCR refers to an exhaust gas purification system that uses ammonia, a decomposition product of urea, as a reducing agent for NOx in exhaust gases. While ammonia can reduce NOx into nitrogen (N2) and water (H2O) with a catalyst, its flammability and toxicity pose safety concerns, making its direct use in automobiles and other applications difficult. However, as mentioned above, urea SCR uses ammonia obtained from the decomposition of urea to reduce NOx, thus offering superior safety. Therefore, urea SCR is widely used in automobiles and thermal power plants. The size of urea SCR varies depending on the application, but the denitrification principle remains the same.

[0004] In large factories, anhydrous ammonia or ammonia solution is sometimes used instead of urea. Anhydrous ammonia, in particular, although highly toxic, can be directly used for NOx reduction. While ammonia solution requires hydrolysis, it is safer than anhydrous ammonia. It is foreseeable that in the future, ammonia will be used as fuel in thermal power plants, industrial furnaces, and ships to reduce CO2 emissions; however, in such cases, the exhaust gas may also contain NOx. Therefore, the demand for various denitrification devices is expected to increase.

[0005] In urea SCR (Self-Repairing Catalytic Reduction), urea or ammonia hardly corrodes stainless steel. However, during the high-temperature decomposition of urea water to generate ammonia, or when unreacted urea water evaporates, substances such as ammonium carbamate are produced, which can corrode stainless steel. Besides being used in commercial vehicles such as buses and trucks that travel long distances, urea SCR is also used in thermal power plants that operate for decades; therefore, high corrosion resistance to these corrosive substances is particularly important.

[0006] Based on the above, for example, in catalyst carriers used in denitrification devices such as urea SCR, stainless steel with excellent corrosion resistance has been applied, and several technologies described below have been disclosed.

[0007] For example, Patent Document 1 discloses a ferritic stainless steel as a material for urea SCR, which ensures the corrosion resistance of the base material and the welded metal by controlling the content of C, N, Ti, Nb, Cr and Mo in the base material.

[0008] Patent document 2 discloses a ferritic stainless steel as a material for urea SCR, which ensures corrosion resistance by controlling the total amount of Ni and Co in the base material within a certain range.

[0009] Patent document 3 discloses a ferritic stainless steel as a material for urea SCR, which ensures corrosion resistance by controlling the concentrations of C, N, Ti and Nb in the base material within a certain range.

[0010] Patent document 4 discloses a ferritic stainless steel as a material for urea SCR, which ensures corrosion resistance by controlling the concentrations of Cr, Si, Al, Ti, Mn and Fe on the surface of the base material within a certain range.

[0011] Patent document 5 discloses a ferritic stainless steel as a material for urea SCR, which ensures corrosion resistance by controlling the total amount of Cr, Si and Mn in the base material within a certain range.

[0012] Prior art literature

[0013] Patent documents

[0014] Patent Document 1: Japanese Patent Application Publication No. 2022-115553

[0015] Patent Document 2: Japanese Patent Application Publication No. 2018-168415

[0016] Patent Document 3: International Publication No. 2016 / 035241

[0017] Patent Document 4: Japanese Patent Application Publication No. 2012-112025

[0018] Patent Document 5: Japanese Patent Application Publication No. 2009-242933 Summary of the Invention

[0019] However, the technologies described in Patent Documents 1-5 only describe the composition of the base material and the weld metal, without considering the degradation of corrosion resistance caused by changes in microstructure during high-temperature use. In recent years, the operating temperature of denitrification devices has been increasing compared to the past. For example, in automobiles, the operating temperature of urea SCRs is also increasing due to the rising exhaust gas temperature. Therefore, after prolonged use at high temperatures, a new problem of reduced corrosion resistance has emerged.

[0020] The present invention was made in view of the above circumstances, and its object is to provide a ferritic stainless steel for denitrification devices that has excellent corrosion resistance in the operating environment of denitrification devices.

[0021] Furthermore, in this specification, excellent corrosion resistance in the operating environment of the denitrification unit refers to a corrosion rate of 0.5 g / (m²) after being kept at 700°C for 1000 hours, according to the Huey test performed according to JIS G 0573:1999 (65% nitric acid corrosion test method for stainless steel). h) and below.

[0022] Technical solutions to solve technical problems

[0023] The Huey test is commonly used to evaluate the corrosion resistance of stainless steel in the operating environment of denitrification equipment. The inventors prepared ferritic stainless steels with various alloy compositions, maintained them at 700°C for 1000 hours, and then conducted Huey tests to investigate the effect of alloy composition on corrosion resistance under these conditions. The results showed that under these conditions, higher Cr content resulted in better corrosion resistance, while higher Nb, Mo, and Si content tended to decrease corrosion resistance.

[0024] The inventors further discovered that when the amount of Laves phase, an intermetallic compound composed of Fe, Nb, Mo, and Si, is low in grain boundary precipitation, the urea SCR denitrification unit exhibits good corrosion resistance in its operating environment. This invention is based on the above insights and further research. The key features of this invention are as follows.

[0025] This invention was completed based on the above insights and further research. Specifically, the key elements of this invention are as follows.

[0026] [1] A ferritic stainless steel for a denitrification device, comprising, by mass%,:

[0027] C: 0.003~0.030%

[0028] N: below 0.030%

[0029] Si: 0.20~1.00%

[0030] Mn: 0.05~0.50%,

[0031] P: below 0.050%

[0032] S: Below 0.020%

[0033] Cr: 13.0~21.0%,

[0034] Mo: 0.001~3.00%

[0035] Al: 0.001~0.50%

[0036] Nb: 0.001–0.60%, and

[0037] Ti: 0.001~0.15%,

[0038] It satisfies the following equations (1) and (2), and the remainder consists of Fe and unavoidable impurities;

[0039] (Ti+Nb×47 / 97) / (8×(C+N)) ≥ 1.0...(1)

[0040] Cr-12Nb-2.0Mo-Si ≥ 10.0...(2)

[0041] In equations (1) and (2), Ti, Nb, C, N, Cr, Mo and Si represent the content (mass%) of each element.

[0042] [2] The ferritic stainless steel for denitrification devices described in [1] also contains, by mass percent, one or more of the following groups A and B:

[0043] Group A: Selected from one or more of the following: Ni: 0.001–1.00%, Cu: 0.01–2.00%, Co: 0.01–1.00%, W: 0.01–2.00%;

[0044] Group B: Selected from one or more of the following: V: 0.01–0.20%, Zr: 0.01–0.50%, Mg: 0.0005–0.0050%, Ca: 0.0005–0.0050%, B: 0.0005–0.0050%, REM (rare earth metals): 0.001–0.100%, Sn: 0.001–0.100%, Sb: 0.001–0.100%.

[0045] [3] The grain boundary coverage of the Laves phase in the ferritic stainless steel for denitrification apparatus described in [1] or [2] after being kept at 700°C for 1000 hours is less than 20%.

[0046] According to the present invention, a ferritic stainless steel for denitrification devices can be provided, which has excellent corrosion resistance in the operating environment of the denitrification device. Detailed Implementation

[0047] The present invention will now be described in detail.

[0048] First, the reasons for defining the composition of steel in this invention will be explained. Furthermore, the content of elements in the steel composition is expressed in "mass%" and will be indicated as "%" hereafter, unless otherwise stated.

[0049] C: 0.003~0.030%

[0050] Increasing the carbon (C) content improves strength, while decreasing it improves processability. Here, to obtain sufficient strength, the C content needs to be 0.003% or more. However, when the C content exceeds 0.030%, the decrease in processability becomes significant, and Cr carbides precipitate at grain boundaries, causing sensitization and reducing corrosion resistance. Therefore, the C content is set in the range of 0.003% to 0.030%. The C content is preferably 0.004% or more. Furthermore, the C content is preferably 0.025% or less, more preferably 0.020% or less, and even more preferably 0.010% or less.

[0051] N: below 0.030%

[0052] When the nitrogen (N) content exceeds 0.030%, corrosion resistance and processability decrease. Therefore, the N content is set to 0.030% or less. Preferably, the N content is 0.025% or less. More preferably, the N content is 0.020% or less. Furthermore, there is no particular limitation on the lower limit of the N content, but excessive reduction in the N content will lead to increased costs; therefore, the N content is preferably 0.003% or more.

[0053] Si: 0.20~1.00%

[0054] Si is a useful deoxidizing element. Its effect is achieved by containing 0.20% or more Si. However, when the Si content exceeds 1.00%, the precipitation of the Laves phase becomes excessive, reducing corrosion resistance. Therefore, the Si content is set in the range of 0.20% to 1.00%. The Si content is preferably 0.25% or more, more preferably 0.30% or more, and even more preferably 0.40% or more. Furthermore, the Si content is preferably 0.80% or less, more preferably 0.70% or less, and even more preferably 0.60% or less.

[0055] Mn: 0.05~0.50%

[0056] Mn has a deoxidizing effect, which is achieved by containing 0.05% or more Mn. However, when the Mn content exceeds 0.50%, it promotes the precipitation of MnS, reducing corrosion resistance. Therefore, the Mn content is set in the range of 0.05% to 0.50%. The Mn content is preferably 0.10% or more, more preferably 0.15% or more. Furthermore, the Mn content is preferably 0.40% or less, more preferably 0.30% or less.

[0057] P: below 0.050%

[0058] Phosphorus (P) is an unavoidable element in steel, but excessive amounts can easily cause intergranular corrosion. This tendency becomes significant when the P content exceeds 0.050%. Therefore, the P content is set to 0.050% or less. Preferably, the P content is 0.030% or less. Furthermore, there is no particular limitation on the lower limit of the P content. However, excessive P removal leads to increased costs, so the P content is preferably 0.005% or more.

[0059] S: below 0.020%

[0060] Sulfur (S) is an unavoidable element in steel. When the S content exceeds 0.020%, it promotes the precipitation of MnS, reducing corrosion resistance. Therefore, the S content is set to 0.020% or less. Preferably, the S content is 0.010% or less. Furthermore, there is no particular limitation on the lower limit of the S content. However, excessive desaturation leads to increased costs, so the S content is preferably 0.0005% or more.

[0061] Cr: 13.0~21.0%

[0062] Cr is an important element for ensuring the corrosion resistance of stainless steel. When the Cr content is below 13.0%, sufficient corrosion resistance cannot be obtained. On the other hand, when the Cr content exceeds 21.0%, the workability decreases. The Cr content is preferably 15.0% or more, more preferably 17.0% or more. Furthermore, the Cr content is preferably 20.0% or less, more preferably 19.0% or less.

[0063] Mo: 0.001~3.00%

[0064] Mo stabilizes the passivation film on stainless steel, improving its corrosion resistance. This effect is achieved when the Mo content is 0.001% or higher. However, when the Mo content exceeds 3.00%, the precipitation of the Laves phase becomes excessive, reducing corrosion resistance in the denitrification unit's operating environment. Therefore, the Mo content is set in the range of 0.001% to 3.00%. The Mo content is preferably 0.50% or higher, more preferably 1.00% or higher. Furthermore, the Mo content is preferably 2.50% or lower, more preferably 2.00% or lower.

[0065] Al: 0.001~0.50%

[0066] Al is a useful deoxidizing element, and its effectiveness is achieved by containing more than 0.001% Al. However, Al is a highly reactive element to oxygen, and processability decreases when the Al content exceeds 0.50%. Therefore, the Al content is set in the range of 0.001% to 0.50%. Preferably, the Al content is below 0.015%.

[0067] Nb: 0.001~0.60%

[0068] By combining with C and N, nitrogen (Nb) is an element that suppresses the decrease in corrosion resistance (sensitization) caused by the precipitation of Cr carbonitrides. It is also an element that effectively improves high-temperature strength. This effect is achieved when the Nb content is 0.001% or higher. On the other hand, when the Nb content exceeds 0.60%, the precipitation of the Laves phase becomes excessive, reducing corrosion resistance in the denitrification unit's operating environment. Therefore, the Nb content is set in the range of 0.001% to 0.60%. The Nb content is preferably 0.10% or higher, more preferably 0.30% or higher. Furthermore, the Nb content is preferably 0.50% or lower, more preferably 0.40% or lower.

[0069] Ti: 0.001~0.15%

[0070] Ti has the effect of combining with C and N contained in steel to prevent sensitization. This effect is achieved by containing 0.001% or more Ti. On the other hand, excessive Ti will reduce workability, so the upper limit must be set at 0.15%. Therefore, the Ti content is set in the range of 0.001% to 0.15%. The Ti content is preferably 0.01% or more, more preferably 0.05% or more. In addition, the Ti content is preferably 0.08% or less.

[0071] (Ti+Nb×47 / 97) / (8×(C+N)) ≥ 1.0...(1)

[0072] In formula (1), Ti, Nb, C and N represent the content (mass%) of each element.

[0073] To ensure corrosion resistance in the operating environment of the denitrification unit, the above formula (1) must be satisfied. When the value of Ti+Nb×47 / 97 is lower than the value of 8×(C+N), Cr carbonitrides precipitate at the grain boundaries, forming a Cr-deficient layer around them, which significantly reduces corrosion resistance. When the value of Ti+Nb×47 / 97 is higher than the value of 8×(C+N), that is, when (Ti+Nb×47 / 97) / (8×(C+N)) ≥ 1.0, Ti and Nb replace Cr to form carbonitrides, which can suppress the formation of a Cr-deficient layer. (Ti+Nb×47 / 97) / (8×(C+N)) is preferably 1.25 or higher. In addition, there is no particular upper limit for (Ti+Nb×47 / 97) / (8×(C+N)). As an example, (Ti+Nb×47 / 97) / (8×(C+N)) can be 3.00 or lower.

[0074] Cr-12Nb-2.0Mo-Si ≥ 10.0...(2)

[0075] In formula (2), Cr, Nb, Mo and Si represent the content (mass%) of each element.

[0076] The inventors have discovered the following: By adjusting the content of Cr, and the contents of Nb, Mo, and Si (which are Laves phase forming elements) to specified ranges, and ensuring that Cr-12Nb-2.0Mo-Si is 10.0% (by mass) or higher, the corrosion resistance in the denitrification unit's operating environment becomes excellent. The reason for this is not yet clear, but it is known that intergranular corrosion occurs in the operating environment of denitrification units. Furthermore, the Laves phase readily dissolves and precipitates at grain boundaries in this environment; therefore, it is speculated that an increase in Laves phase precipitation would promote intergranular corrosion. By reducing the contents of Nb, Mo, and Si, the precipitation of the Laves phase can be suppressed, thus contributing to improved corrosion resistance. On the other hand, the inventors have found that while Cr increases the precipitation of the Laves phase, it also improves the corrosion resistance of the Laves phase; therefore, from the viewpoint of corrosion resistance, a higher Cr content is preferred. Therefore, in this invention, the contents of Cr, Nb, Mo, and Si are each set within the aforementioned ranges, and the content of Cr-12Nb-2.0Mo-Si is 10.0 or more. As a result, even when heated for extended periods within the operating temperature range of the denitrification device (300–700°C), the precipitation of the Laves phase can be suppressed, maintaining excellent corrosion resistance. The content of Cr-12Nb-2.0Mo-Si is preferably 12.0 or more. Furthermore, the upper limit of Cr-12Nb-2.0Mo-Si is not particularly limited; as an example, Cr-12Nb-2.0Mo-Si can be 16.0 or less, or 15.0 or less.

[0077] The basic components (essential components) of the ferritic stainless steel for the denitrification device of the present invention (hereinafter also simply referred to as the ferritic stainless steel of the present invention) have been described above. In the composition of the ferritic stainless steel of the present invention, the remainder other than the above-described components may be Fe and unavoidable impurities.

[0078] In addition, in this invention, the above-mentioned components may contain one or more groups selected from Group A and Group B.

[0079] Group A: Selected from one or more of the following: Ni: 0.001–1.00%, Cu: 0.01–2.00%, Co: 0.01–1.00%, W: 0.01–2.00%;

[0080] Group B: Selected from one or more of the following: V: 0.01–0.20%, Zr: 0.01–0.50%, Mg: 0.0005–0.0050%, Ca: 0.0005–0.0050%, B: 0.0005–0.0050%, REM (rare earth metals): 0.001–0.100%, Sn: 0.001–0.100%, Sb: 0.001–0.100%.

[0081] Ni: 0.001~1.00%

[0082] Regarding Ni, although the reasons are not yet clear, a content of 0.001% or more is beneficial for improving corrosion resistance. On the other hand, when the Ni content exceeds 1.00%, the processability deteriorates. Therefore, in the case of Ni content, the Ni content is set in the range of 0.001% to 1.00%. In the case of Ni content, a Ni content of 0.05% or more is more preferred. Furthermore, in the case of Ni content, a Ni content of 0.70% or less is more preferred.

[0083] Cu: 0.01~2.00%

[0084] Cu is an element that improves corrosion resistance. This effect is achieved when the Cu content is 0.01% or higher. However, when the Cu content exceeds 2.00%, the precipitation of the ε phase actually reduces corrosion resistance. Therefore, in the case of Cu, the Cu content is set in the range of 0.01% to 2.00%.

[0085] Co: 0.01~1.00%

[0086] Co is an element that improves corrosion resistance. This effect is achieved when the Co content is 0.01% or higher. However, when the Co content exceeds 1.00%, processability decreases. Therefore, when Co is present, the Co content is set in the range of 0.01% to 1.00%. More preferably, the Co content is 0.05% or higher. Furthermore, more preferably, the Co content is 0.70% or lower.

[0087] W: 0.01~2.00%

[0088] W is an element that improves corrosion resistance. This effect is achieved when the W content is 0.01% or more. However, when the W content exceeds 2.00%, the Laves phase precipitates excessively, reducing processability. Therefore, when W is present, the W content is set in the range of 0.01% to 2.00%. More preferably, the W content is 0.05% or more. Furthermore, more preferably, the W content is 1.00% or less.

[0089] V: 0.01~0.20%

[0090] Like Ti, V combines with C and N in the steel to prevent sensitization. This effect is achieved when the V content is 0.01% or more. On the other hand, when the V content exceeds 0.20%, the workability decreases. Therefore, when V is present, the V content is set in the range of 0.01% to 0.20%. When V is present, the V content is more preferably 0.15% or less, and even more preferably 0.10% or less.

[0091] Zr: 0.01~0.50%

[0092] Like Ti and Nb, Zr is an element that combines with C and N in steel to suppress sensitization. This effect is achieved when the Zr content is 0.01% or higher. On the other hand, when the Zr content exceeds 0.50%, the workability decreases. Therefore, when Zr is present, the Zr content is set in the range of 0.01% to 0.50%. More preferably, the Zr content is 0.03% or higher. Furthermore, more preferably, the Zr content is 0.20% or lower.

[0093] Mg: 0.0005~0.0050%

[0094] Mg acts as a deoxidizer. This effect is achieved when the Mg content is 0.0005% or higher. However, when the Mg content exceeds 0.0050%, the toughness and manufacturability of the steel decrease. Therefore, in the case of Mg content, the Mg content is set in the range of 0.0005% to 0.0050%. In the case of Mg content, it is more preferable to have a Mg content of 0.0020% or less.

[0095] Ca: 0.0005~0.0050%

[0096] Ca improves the penetration depth of welds and enhances weldability. This effect is achieved when the Ca content is 0.0005% or higher. However, when the Ca content exceeds 0.0050%, it combines with S to form CaS, which reduces corrosion resistance. Therefore, in cases where Ca is present, the Ca content is set in the range of 0.0005% to 0.0050%. More preferably, the Ca content is 0.0010% or higher. Furthermore, more preferably, the Ca content is 0.0040% or lower.

[0097] B: 0.0005~0.0050%

[0098] Boron (B) is an element that improves brittleness during secondary processing. Its effect is evident when the B content is above 0.0005%. However, when the B content exceeds 0.0050%, ductility decreases due to solid solution strengthening. Therefore, in cases where B is present, the B content is set within the range of 0.0005% to 0.0050%.

[0099] REM (Rare Earth Metals): 0.001~0.100%

[0100] Rare earth metals (REMs) are effective deoxidizing elements. This effect is achieved when the REM content is 0.001% or higher. However, when the REM content exceeds 0.100%, hot workability decreases. Therefore, when REMs are present, the REM content is set in the range of 0.001% to 0.100%. More preferably, the REM content is 0.010% or higher. Furthermore, more preferably, the REM content is 0.050% or lower. Additionally, REM is a collective term for 15 elements, including Sc, Y, and lanthanum (La) from atomic number 57 to lutetium (Lu) from atomic number 71; the REM content mentioned here refers to the total content of these elements.

[0101] Sn: 0.001~0.100%

[0102] Sn is an effective element for suppressing surface roughness during processing. This effect is achieved when the Sn content is 0.001% or higher. However, when the Sn content exceeds 0.100%, hot workability decreases. Therefore, when Sn is present, the Sn content is set in the range of 0.001% to 0.100%. More preferably, the Sn content is 0.050% or less.

[0103] Sb: 0.001~0.100%

[0104] Like Sn, Sb is an effective element for suppressing surface roughness in processed surfaces. This effect is achieved when the Sb content is 0.001% or higher. However, when the Sb content exceeds 0.100%, processability decreases. Therefore, in cases where Sb is present, the Sb content is set in the range of 0.001% to 0.100%. More preferably, the Sb content is 0.050% or less.

[0105] In addition, when the contents of Ni, Cu, Co, W, V, Zr, Mg, Ca, B, REM, Sn, and Sb described as any of the above components are lower than the above lower limit values, these components are contained as unavoidable impurities.

[0106] Laves phase grain boundary coverage: below 20% (preferred condition)

[0107] The inventors have discovered that by suppressing the precipitation of the Laves phase at grain boundaries, corrosion resistance in the operating environment of denitrification equipment can be improved. In particular, it was found that if the grain boundary coverage of the Laves phase is below 20%, excellent corrosion resistance in the operating environment of the denitrification equipment can be more consistently ensured. The rationale is not yet clear, but grain boundary corrosion is known to occur in the operating environment of denitrification equipment. Furthermore, the Laves phase readily dissolves and precipitates at grain boundaries in this environment; therefore, it is speculated that increased Laves phase precipitation would promote grain boundary corrosion. Here, the operating environment of the urea SCR component is approximately 700°C in the high-temperature section. Therefore, it is preferable to set the grain boundary coverage of the Laves phase in the ferritic stainless steel after being held at 700°C for 1000 hours to be below 20%. The lower the grain boundary coverage, the more preferred; it can also be 0%.

[0108] Here, the grain boundary coverage of the Laves phase was evaluated using the following method. Samples were collected from steel that had been held at 700°C for 1000 hours, with a longitudinal section as the observation surface. The samples were then resin-embedded and mirror-polished. Next, reflection electron microscopy (SEM) images were obtained, with five arbitrary locations observed at 1000x magnification (with a field of view of at least 100 μm × 100 μm). Within a 100 μm × 100 μm region at the center of each SEM image, the total length L of the grain boundaries covered by the Laves phase was calculated. Laves Relative to the total grain boundary length L GB The proportion is defined as the grain boundary coverage of the Laves phase, as shown in equation (3). The average value of the grain boundary coverage of the Laves phase obtained from the above 5 locations is taken as the grain boundary coverage (%) of the Laves phase in the ferritic stainless steel.

[0109] Laves phase grain boundary coverage (%) = (total grain boundary length L covered by Laves phase) Laves / Total grain boundary length L GB )×100 ...(3)

[0110] Next, a preferred method for manufacturing the ferritic stainless steel of the present invention will be described. The method for manufacturing the ferritic stainless steel of the present invention is not particularly limited, and for example, it can be manufactured as follows: A steel billet having the above-described composition is hot-rolled into a hot-rolled sheet, and the hot-rolled sheet is then hot-rolled and annealed as needed. Then, the hot-rolled sheet or the hot-rolled and annealed sheet is cold-rolled to produce a cold-rolled sheet of the desired thickness, and further, the cold-rolled sheet is cold-rolled and annealed as needed, thereby manufacturing a ferritic stainless steel sheet having the above-described composition. Furthermore, the conditions for hot rolling and cold rolling, hot-rolled sheet annealing, and cold-rolled sheet annealing are not particularly limited, and can be carried out according to conventional methods.

[0111] The steelmaking process preferably involves secondary refining of steel smelted in a converter or electric furnace using a VOD (Vacuum Oxygen Decarburization) method to produce steel containing the aforementioned essential components and any other components as needed. The molten steel can be processed into finished steel products using known methods, but continuous casting is preferred for both productivity and quality considerations. The steel is then preferably heated to 1050–1250°C and hot-rolled into hot-rolled plates of the desired thickness. Alternatively, hot working can be performed in addition to plate production. The hot-rolled plates are then, as needed, preferably continuously annealed at 900–1150°C and descaled by pickling or similar methods to produce hot-rolled products. Furthermore, if necessary, oxide scale can be removed before pickling by shot peening or grinding with a grinding brush.

[0112] Furthermore, the aforementioned hot-rolled products (hot-rolled annealed sheets, etc.) can be processed into cold-rolled products through processes such as cold rolling. In this case, cold rolling can be performed once, but from the viewpoint of productivity and required quality, it can also be performed two or more times, including intermediate annealing. The total reduction rate of one or more cold rolling processes is preferably 60% or more, more preferably 70% or more. The cold-rolled steel sheet is then preferably subjected to continuous annealing (final annealing) at a temperature of 900–1150°C, more preferably 950–1150°C, followed by pickling to produce a cold-rolled product. Alternatively, continuous annealing can be performed during bright annealing, omitting pickling. Furthermore, after final annealing, leveling rolling or similar processes can be performed to adjust the shape, surface roughness, and material of the steel sheet.

[0113] The ferritic stainless steel of the present invention described above is suitable for denitrification devices such as urea SCR.

[0114] Example

[0115] Steel with the composition shown in Table 1 was melted in a vacuum melting furnace and heated at 1150°C for 1 hour, followed by hot rolling to produce a hot-rolled sheet with a thickness of 4.0 mm. After annealing the hot-rolled sheet at 1080°C for 1 minute, the surface oxide scale was removed by grinding, and the sheet was cold-rolled to a thickness of 1.0 mm to obtain a cold-rolled sheet. The cold-rolled sheet was then subjected to a final annealing at 1040°C for 1 minute in an ammonia decomposition gas atmosphere to produce a cold-rolled annealed sheet.

[0116] The cold-rolled annealed sheet obtained above was subjected to a heat treatment at 700°C for 1000 hours in atmospheric conditions. Then, it was cooled to room temperature, its surface was sanded to 600 grit, and degreased with acetone. For the samples prepared in this way, the grain boundary coverage of the Laves phase and the corrosion resistance in the denitrification unit's operating environment were determined as follows. The results are shown in Table 2.

[0117] Laves phase grain boundary coverage

[0118] From the prepared sample, samples were collected using a longitudinal section as the observation surface. After resin embedding and mirror polishing, the samples were observed using SEM reflectance electron microscopy (SEM) at 1000x magnification at five arbitrary locations. The total grain boundary length L covered by the Laves phase in a 100μm × 100μm region at the center of each image was determined. Laves Relative to the total grain boundary length L GB The proportion of the Laves phase is calculated using equation (3) above. The average value of the Laves phase grain boundary coverage calculated at the five locations is taken as the Laves phase grain boundary coverage of the sample. The Laves phase grain boundary coverage is evaluated according to the following criteria.

[0119] ○: 20% or less

[0120] ×: More than 20%

[0121] Corrosion resistance evaluation of denitrification unit in operating environment (Huey test)

[0122] From the prepared sample, test pieces with a width of 20 mm and a length of 50 mm were cut out, and Huey tests were performed according to JIS G 0573:1999 (65% nitric acid corrosion test method for stainless steel). The solution used was 65% nitric acid, and the test was conducted at boiling. Three cycles of 48 hours each were performed. After each cycle, the weight was measured using an electronic balance, and the corrosion rate (g / (m²)) was calculated from the weight change before and after the test. h), the average value of 3 cycles is taken as the corrosion rate of the sample. The corrosion rate is evaluated according to the following criteria: ○ is acceptable, × is unacceptable.

[0123] ○: 0.5g / (m²) h) below

[0124] ×: Exceeding 0.5g / (m²) h)

[0125]

[0126]

[0127] As shown in Table 2, Invention Examples No. 1 to 26 exhibit good corrosion resistance in the operating environment of the denitrification device. In contrast, Comparative Examples No. 27 to 35, whose composition is outside the appropriate range, failed to meet the corrosion resistance target in the operating environment of the denitrification device.

[0128] Specifically, in Comparative Example No. 27 (steel symbol B1), the Mo content exceeded the upper limit of the present invention, and therefore excellent corrosion resistance was not achieved in the operating environment of the denitrification unit. In Comparative Example No. 27, the grain boundary coverage of the Laves phase exceeded 20%.

[0129] In Comparative Example No. 28 (steel symbol B2), the Nb content exceeded the upper limit of the present invention, and therefore excellent corrosion resistance was not achieved in the operating environment of the denitrification unit. In Comparative Example No. 28, the grain boundary coverage of the Laves phase exceeded 20%.

[0130] In Comparative Example No. 29 (steel symbol B3), the Si content exceeded the upper limit of the present invention, and therefore excellent corrosion resistance was not achieved in the operating environment of the denitrification unit. In Comparative Example No. 29, the grain boundary coverage of the Laves phase exceeded 20%.

[0131] In Comparative Example No. 30 (steel symbol B4), the Mn content exceeded the upper limit of the present invention, and therefore failed to obtain excellent corrosion resistance in the operating environment of the denitrification device.

[0132] In Comparative Example No. 31 (steel symbol B5), the C content exceeded the upper limit of the present invention, and therefore excellent corrosion resistance was not obtained in the operating environment of the denitrification device.

[0133] In Comparative Example No. 32 (steel symbol B6), the nitrogen content exceeded the upper limit of the present invention, and therefore excellent corrosion resistance was not obtained in the operating environment of the denitrification device.

[0134] In Comparative Example No. 33 (steel symbol B7), the Cr content was lower than the lower limit of the present invention, and therefore excellent corrosion resistance was not obtained in the operating environment of the denitrification device.

[0135] In Comparative Example No. 34 (steel symbol B8), all components are within the specified range, but it does not satisfy equation (1), and therefore fails to achieve excellent corrosion resistance in the operating environment of the denitrification unit.

[0136] In Comparative Example No. 35 (steel symbol B9), all components were within the specified range, but equation (2) was not satisfied, therefore excellent corrosion resistance was not achieved in the operating environment of the denitrification unit. In Comparative Example No. 35, the grain boundary coverage of the Laves phase exceeded 20%.

[0137] Industrial availability

[0138] According to the present invention, ferritic stainless steel with excellent corrosion resistance in the operating environment of denitrification equipment can be provided, and is therefore extremely useful in industry.

Claims

1. A ferritic stainless steel for a denitrification device, having the following composition: Contains, by mass% C:0.003~0.030%、 N: below 0.030% Si: 0.20~1.00% Mn: 0.05~0.50%, P: below 0.050% S: Below 0.020% Cr:13.0~21.0%、 Mo: 0.001~3.00% Al:0.001~0.50%、 Nb: 0.001–0.60%, and Ti: 0.001~0.15%, Furthermore, satisfying equations (1) and (2) below, the remainder consists of Fe and unavoidable impurities; (Ti+Nb×47 / 97) / (8×(C+N))≥1.0...(1) Cr-12Nb-2.0Mo-Si≥10.0...(2) in, In equations (1) and (2), Ti, Nb, C, N, Cr, Mo and Si represent the mass percentage of each element.

2. The ferritic stainless steel for the denitrification device according to claim 1, further comprising, by mass%, one or more components selected from group A and group B below: Group A: Selected from one or more of the following: Ni: 0.001–1.00%, Cu: 0.01–2.00%, Co: 0.01–1.00%, W: 0.01–2.00%; Group B: Selected from one or more of the following: V: 0.01–0.20%, Zr: 0.01–0.50%, Mg: 0.0005–0.0050%, Ca: 0.0005–0.0050%, B: 0.0005–0.0050%, REM rare earth metals: 0.001–0.100%, Sn: 0.001–0.100%, Sb: 0.001–0.100%.

3. The ferritic stainless steel for denitrification devices according to claim 1 or 2, wherein the grain boundary coverage of the Laves phase after being held at 700°C for 1000 hours is less than 20%.

Citation Information

Patent Citations

  • Separation of dl-threonine and dl-allothreonine

    CA500050A

  • Ferritic stainless steel having excellent corrosion resistance in urea water

    JP2009242933A

  • Ferritic stainless steel sheet for part of urea SCR system and method for production thereof

    JP2012112025A

  • Ferritic stainless steel

    JP2018168415A

  • Weld member made of stainless steel for urea SCR system

    JP2022115553A